Walk the talk: coordinating gesture with locomotion for conversational characters. (3rd May 2016) - Wang, Yingying; Ruhland, Kerstin; Neff, Michael; O'Sullivan, Carol
Abstract: Communicative behaviors are a very important aspect of human behavior and deserve special attention when simulating groups and crowds of virtual pedestrians. Previous approaches have tended to focus on generating believable gestures for individual characters and talker‐listener behaviors for static groups. In this paper, we consider the problem of creating rich and varied conversational behaviors for data‐driven animation of walking and jogging characters. We captured ground truth data of participants conversing in pairs while walking and jogging. Our stylized splicing method takes as input a motion captured standing gesture performance and a set of looped full body locomotion clips. Guided by the ground truth metrics, we perform stylized splicing and synchronization of gesture with locomotion to produce natural conversations of characters in motion. Copyright © 2016 John Wiley & Sons, Ltd. Abstract : Communicative behaviors are a very important aspect of human behavior and deserve special attention when simulating groups and crowds of virtual pedestrians. In this paper, we consider the problem of creating rich and varied conversational behaviors for data‐driven animation of walking and jogging characters. Guided by ground truth metrics derived from real video, we perform stylized splicing and synchronization of gesture with locomotion to produce natural conversations of characters in motion.